Effectiveness of car scrappage schemes: Comparative analysis of European countries - Miroslav Svoboda; Michael Fanta; Jan Mošovský (Charles University in Prague, Institute of Economic Studies (IES), 2023)
This study aims to investigate the effectiveness of car scrappage schemes implemented in the European Union (EU) during the economic crisis of 2009. The study uses a synthetic control variable and a difference-in-differences method to evaluate these policies. Using monthly data on new passenger car registrations in European countries, the study examines the impact of the schemes. The results show that the impact of scrappage schemes varies across countries, with statistically significant effects observed in Germany and Slovakia, followed by Greece and Italy, albeit limited in some aspects. The results of the study underline the need for careful policy design and show that the effectiveness of car scrappage schemes goes beyond the level of premiums or budget allocations. It is also influenced by other elements such as the duration of the scheme, the overarching policy environment and the novelty of the implementation strategies.
Keywords: H23; C21; R48; 330; car scrappage schemes; synthetic control method; difference-in-differences